Deuteronomium - gister en vandag - Lion-Cachet, F. N. (Koers, 1988)
In this article the meaning of Deutoronomy is described from the perspective of a revelation-cognitive viewpoint, and attention is directed to the prescriptive character of the book. Deuteronomy has its origin with Moses, but in the course of many years it has been supplemented and actualized. The revelational content testi fies amongst others that Moses is speaking in the name of Vahweh; what the relationship is between Vahweh and the nation; Who He is and what is demanded of each member of the nation; and there is a consideration of the special time-bound determinations which are yet constructed on the basis of firm principles. In the New Testament the power of the Word, as actualized in the teachings of Jesus, can be found again.